2015
DOI: 10.1002/cssc.201500848
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Titania Perovskite Solar Cell Technology for Sustainable Design and Manufacturing

Abstract: Perovskite solar cells have attracted enormous attention in recent years due to their low cost and superior technical performance. However, the use of toxic metals, such as lead, in the perovskite dye and toxic chemicals in perovskite solar cell manufacturing causes grave concerns for its environmental performance. To understand and facilitate the sustainable development of perovskite solar cell technology from its design to manufacturing, a comprehensive environmental impact assessment has been conducted on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 48 publications
6
96
0
Order By: Relevance
“…[25][26][27][28][29] Recently, a comparison of PSCs with silicon solar cells and a tandem with both perovskite and silicon was implemented. 30 Furthermore, the four most common methods to produce PSCs were environmentally revised by us.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] Recently, a comparison of PSCs with silicon solar cells and a tandem with both perovskite and silicon was implemented. 30 Furthermore, the four most common methods to produce PSCs were environmentally revised by us.…”
Section: Introductionmentioning
confidence: 99%
“…Roof integrated a-Si/nc-Si [21], and a-Si/nc-Si [22] have a significant climate change impact. Lastly, one study shows that TiO 2 nanotube based perovskite solar cells have either comparable or worse carbon impacts compared to alternatives [24].…”
Section: Carbon Emissions and Energy Usementioning
confidence: 99%
“…Furthermore, the low deposition rates extend further the deposition time and subsequently, the energy consumption and carbon emissions. Five studies have included balance-of-system (BOS) equipment, which is all the related equipment that is needed to allow the functioning of the photovoltaics, cables, inventers, switches and more, in their system boundaries [17,19,21,22,24]. All the studies have shown that BOS is also a very important contributor for both climate change impact and primary energy consumption.…”
Section: Main Contributors Of Climate Change and Energy Demandmentioning
confidence: 99%
See 2 more Smart Citations